2013
DOI: 10.1186/1471-2369-14-94
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-antineutrophil cytoplasmic antibody-associated crescentic glomerulonephritis in autosomal dominant polycystic kidney disease

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is an inherited disorder that is characterized by the development of cysts in the kidneys and other organs. Urinary protein excretion is usually less than 1 g/day, and ADPKD is rarely associated with nephrotic syndrome or rapidly progressive glomerulonephritis (RPGN). To date, myeloperoxidase (MPO)-antineutrophil cytoplasmic antibody (ANCA)-associated crescentic glomerulonephritis (CrGN) has not been reported in a patient with ADPKD.Case presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Visciano et al listed 29 reported cases of ADPKD with nephrotic syndrome evaluated by renal histopathological studies and illustrated that FSGS was the most common cause of nephrotic syndrome (6 out of 29 cases) [2]. A literature review by Sumida et al observed 19 cases of ADPKD with nephrotic syndrome, whose leading cause was FSGS (4 out of 19 cases) manifesting urine protein excretion of 5.8 to 14 g/day [3]. However, due to the rarity of the disease and limited number of reports, histopathology of ADPKD complicated with nephrotic syndrome has not been entirely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Visciano et al listed 29 reported cases of ADPKD with nephrotic syndrome evaluated by renal histopathological studies and illustrated that FSGS was the most common cause of nephrotic syndrome (6 out of 29 cases) [2]. A literature review by Sumida et al observed 19 cases of ADPKD with nephrotic syndrome, whose leading cause was FSGS (4 out of 19 cases) manifesting urine protein excretion of 5.8 to 14 g/day [3]. However, due to the rarity of the disease and limited number of reports, histopathology of ADPKD complicated with nephrotic syndrome has not been entirely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Usually in this disorder, urinary protein excretion is less than 1 g/24 hour, while nephrotic syndrome is considered to be rare. [ 5 ] The histopathological lesions reported are variously covering focal segmental glomerulosclerosis, [ 6 ] membranous nephropathy, [ 7 ] minimal change disease, [ 8 ] crescentic glomerulonephritis, [ 9 ] immunoglobulin A nephropathy, [ 10 ] amyloidosis, [ 11 ] and mesengioproliferative glomerulonephritis. [ 12 ] It proved to be invalid of hormone empirical therapy for the patient with no sign of proteinuria reducing.…”
Section: Discussionmentioning
confidence: 99%
“…All cases were characterized by nephrotic range proteinuria, hematuria and acute kidney injury indicated by the rapid decline in kidney function. In the most recently reported cases (38), both patients had ANCA-associated crescentic glomerulonephritis without evidence of vasculitis. In the case we presented in this review, the cause of acute kidney injury and nephrotic syndrome was attributed to crescentic glomerulonephritis rather that the patient's underlying polycystic kidney disease.…”
Section: Proliferative Glomerulonephritis In Adpkdmentioning
confidence: 99%